ESPEN practical guideline: Home enteral nutrition. Issue 2 (February 2022) - Bischoff, Stephan C.; Austin, Peter; Boeykens, Kurt; Chourdakis, Michael; Cuerda, Cristina; Jonkers-Schuitema, Cora; Lichota, Marek; Nyulasi, Ibolya; Schneider, Stéphane M.; Stanga, Zeno; Pironi, Loris
Summary: This ESPEN practical guideline will inform physicians, nurses, dieticians, pharmacists, caregivers and other home enteral nutrition (HEN) providers in a concise way about the indications and contraindications for HEN, as well as its implementation and monitoring. This guideline will also inform interested patients requiring HEN. Home parenteral nutrition is not included but will be addressed in a separate ESPEN guideline. The guideline is based on the ESPEN scientific guideline published before, which consists of 61 recommendations that have been reproduced and renumbered, along with the associated commentaries that have been shorted compared to the scientific guideline. Evidence grades and consensus levels are indicated. The guideline was commissioned and financially supported by ESPEN and the members of the guideline group were selected by ESPEN.